2012
DOI: 10.1016/j.eplepsyres.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia enhances high-voltage-activated calcium currents in rat primary cortical neurons via calcineurin

Abstract: Hypoxia regulates neuronal ion channels, sometimes resulting in seizures. We evaluated the effects of brief sustained hypoxia (1% O2, 4 h) on voltage-gated calcium channels (VGCCs) in cultured rat primary cortical neurons. High-voltage activated (HVA) Ca2+ currents were acquired immediately after hypoxic exposure or after 48 h recovery in 95% air/5% CO2. Maximal Ca2+ current density increased 1.5-fold immediately after hypoxia, but reverted to baseline after 48 h normoxia. This enhancement was primarily due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…While Nav channels themselves pass essentially no Ca ++ [50], Nav channel activity would activate any voltage-dependent Ca ++ channels [51]. With this in mind we also investigated the effect of the Nav channel agonist, veratridine, on neurotoxicity and the mechanical properties of neurons, selecting initial concentrations based on previous studies [52].…”
Section: Resultsmentioning
confidence: 99%
“…While Nav channels themselves pass essentially no Ca ++ [50], Nav channel activity would activate any voltage-dependent Ca ++ channels [51]. With this in mind we also investigated the effect of the Nav channel agonist, veratridine, on neurotoxicity and the mechanical properties of neurons, selecting initial concentrations based on previous studies [52].…”
Section: Resultsmentioning
confidence: 99%
“…) and cortical neurons (Xiang et al . ). Administration of nimodipine attenuated cytosolic calcineurin activity in the hippocampus of aged rats (Foster et al .…”
Section: Discussionmentioning
confidence: 97%
“…A c c e p t e d M a n u s c r i p t 13 demonstrated there were no differences in behavioral seizures between rats that did or did not receive FK506 after termination of SE. However, we found that FK506 markedly inhibited brain focal edema, brain water content and astrogliosis, indicating that SE induced CaN activity and CaN concentration increase and CaN further participated in a series of pathological process after SE [13,14,15].…”
Section: S T a C C E P T E Dmentioning
confidence: 85%
“…However, we found that FK506 markedly inhibited brain focal edema, brain water content and astrogliosis, indicating that SE induced CaN activity and CaN concentration increase and CaN further participated in a series of pathological process after SE [13,14,15].…”
Section: S T a C C E P T E Dmentioning
confidence: 90%